Annual Report 2021: Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) - Accelerating Impacts of CGIAR Climate Research for Africa (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) is a project that’s administered by the Alliance of Bioversity International and the International Center for Tropical Agriculture (CIAT).